2019
DOI: 10.1016/j.ijmultiphaseflow.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the jamming of particles in a three-dimensional fluid-driven flow via coupled CFD–DEM simulations

Abstract: The clogging of a dense stream of particles when passing through an orifice occurs ubiquitously in both natural and industrial fields. Since most of the jamming phenomena lead to the negative effects, studying and preventing jamming is of great importance. There are two typical types of jamming due to different types of driving force: (a) gravity-driven jamming and (b) fluid-driven jamming. Among these two types of jamming, the fluid-driven jamming occurs in fluid-driven particle flows, and the initial solid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…This approach was subsequently adopted in computational fluid dynamics-discrete element method (CFD-DEM) simulations of a particle monolayer at a channel step-constriction [5]. Methodologically similar CFD-DEM approaches have been adopted in a 3D flow from a square channel to a circular orifice [6], as well as that of a particle monolayer in a tapered channel [7]. Limited other research [8], however, has gone into fitting jamming probabilities with functions.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was subsequently adopted in computational fluid dynamics-discrete element method (CFD-DEM) simulations of a particle monolayer at a channel step-constriction [5]. Methodologically similar CFD-DEM approaches have been adopted in a 3D flow from a square channel to a circular orifice [6], as well as that of a particle monolayer in a tapered channel [7]. Limited other research [8], however, has gone into fitting jamming probabilities with functions.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research based on numerical simulation methods has been conducted. The numerical simulations can be divided into several types, such as the particle quasi‐fluid method, CFD‐DEM method (including LBM‐DEM, LES‐DEM, and DNS‐IB), particle tracking method, and Brownian dynamics simulation . The existing studies demonstrated that the numerical simulation is an effective means to study the particulate suspensions transport and permeability damage to the porous media.…”
Section: Introductionmentioning
confidence: 99%
“…The existing studies demonstrated that the numerical simulation is an effective means to study the particulate suspensions transport and permeability damage to the porous media. The particle size‐exclusion mechanism in a smooth fracture with a constrict has been extensively studied, and the general conclusion of these studies is that mechanical bridging is more prone to occur when the particle size is larger than one‐third of the fracture width . The phenomena of particle penetration and mud cake formation in packed beds have been studied widely .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations